Doble arco aórtico en Honduras: causa inusual de disfagia en paciente adulto. Un reporte de caso - Bock Alvarado, Skarleth Paola (2025)
Vascular rings represent less than 1% of congenital cardiovascular anomalies, with double aorticarch being the most common variant. It is typically diagnosed in infants, with respiratory symptomsin over 90% of cases. We present the case of a 31-year-old male patient with recurrent childhoodrespiratory infections and asthma, who presented with progressive dysphagia. Contrast-enhancedcomputed tomography angiography revealed a double aortic arch with right-sided dominance, andthe esophagram revealed compression of the proximal third of the esophagus. A left posterolateralthoracotomy was performed with division of the distal left arch, division of the ligamentum arteriosum,adhesions release, and thoracic aorta reconstruction. Postoperative recovery was favorable, withcomplete resolution of symptoms. Double aortic arch is rarely diagnosed in adulthood. This casehighlights its atypical presentation, with predominant gastrointestinal symptoms, and the importanceof considering it in the differential diagnosis of dysphagia.